Suicidality Presented to a Child and Adolescent Psychiatry Emergency Service: Increasing Rate and Changing Characteristics - Kandsperger, Stephanie; Jarvers, Irina; Schleicher, Daniel; Ecker, Angelika; Wirth, Michael; Brunner, Romuald (Frontiers in Psychiatry, 2021)
Background: Children and adolescents who present to child and adolescent psychiatric emergency departments show a variety of reasons for their presentations. Suicidality, in particular suicidal thoughts and suicide attempts, as well as non-suicidal self-injury (NSSI) play a large and important role. In this context, inpatient admissions frequently serve as crisis intervention. Methods: In this study, face-to-face emergency presentations to the emergency department at our Clinic of Child and Adolescent Psychiatry (CAP) were analyzed over the years 2014 to 2018, the 4th quarter (October to December) of each year. Data from 902 emergency presentations were evaluated, primarily with regard to suicidal thoughts, suicide attempts, and NSSI as reasons for presentation. Results: Data demonstrated that the number of emergency presentations increased in general and especially for suicidal thoughts and NSSI as reasons for presentation. In addition, suicidal thoughts, suicide attempts and NSSI as reasons for emergency presentation were more likely to result in crisis-related inpatient admissions. Furthermore, reporting suicidal thoughts and suicide attempts at emergency presentation was associated with longer inpatient stays. Finally, cases with multiple diagnoses increased independent of the general increase in emergency presentations. Conclusion: The increase of utilization of clinics with CAP outpatient emergency patients and following admissions to the inpatient units for crisis intervention poses a major challenge for the future. It is important to prepare for the assessment and treatment of suicidality, which is of extraordinary importance in the care of emergency patients.